HERDING BEHAVIOR IN FINANCIAL MARKET – SYSTEMATIC LITERATURE REVIEW - Sibarani, Bintang (Fakultas Ekonomi, Universitas Negeri Jakarta, 2024)
The aim of this research is to present a comprehensive theoretical analysis and provide concrete empirical support pertaining to the phenomenon of herding behavior within financial markets. The current paper can be classified as a literature review, which employed data collection techniques through an extensive survey of existing literature. The body of knowledge accumulated over a span of more than twenty years, consisting of both empirical investigations and theoretical inquiries, has yielded significant insights into the intricate nature of investor herding behavior. However, it is important to acknowledge that the author possesses relatively limited knowledge regarding markets other than capital markets, thereby presenting a constraint in terms of exploring the complexities associated with shifting behavior patterns. Furthermore, the available evidence concerning the existence of following behavior is not particularly compelling. Consequently, this paper advocates for the development and application of an empirical methodology that can effectively address these aforementioned limitations and offer a comprehensive evaluation of herding behavior. Additionally, this study critically examines recent empirical findings in order to identify areas that remain unexplored and require further investigation in future research endeavors.